The Mediating Role of the News in the BP Oil Spill Crisis 2010: How U.S. News Is Influenced by Public Relations and in Turn Influences Public Awareness, Foreign News, and the Share Price. (April 2015) - Kleinnijenhuis, Jan; Schultz, Friederike; Utz, Sonja; Oegema, Dirk
The paper explains antecedents and consequences of news during the BP oil spill crisis by analyzing newspaper and internet coverage as well as financial indicators. The study establishes the roles of routines in financial journalism and of BP's public relations efforts in building the U.S. media agenda. The U.S. media agenda in turn bears a classic agenda-setting effect on public awareness, an intermedia agenda-setting effect on foreign media, and a stakeholder agenda-setting effect on financial markets. A second-level attribute agenda-setting post-hoc study reveals that these first-order agenda setting effects depend on the resonance of specific problems and solutions with specific interests and a specific frame of mind. Financial stakeholders, for example, reacted negatively to news about judicial accountability, but positively to press releases about BP's skills in implementing solutions. The findings contradict research which states that the news in classic media merely mirrors share prices.